From subject to collaborator: Transmedia storytelling and social research. (February 2017) - Hancox, Donna
New media technologies and the narrative turn in qualitative research have expanded the methods through which we gather and share the stories of groups who have traditionally been written about by others rather than telling their own stories to reveal the complexities of their experiences. There is a long tradition in community arts, community development and social activism that posits personal narratives as the building blocks for public understanding of complex social issues. In the fields of community storytelling, documentary and social activism, it is possible to see an emerging intersection between the affordances of digital technologies and the recognition of the stories of marginalized people. This article is particularly interested in the ways storytellers have repurposed the accepted conventions of transmedia storytelling to create projects that are able to offer a multiplicity of voices and to create stories that can represent complex issues without privileging a particular point of view or story form.